Survival Improvement in Patients with Renal Cell Carcinoma and Disparities between Different Sexes, Races, and Socioeconomic Status: 1977–2016. (30th July 2022) - Ouyang, Dijun; Sun, Huanhuan; Chen, Nan; Yan, Yan; Ma, Haiqing; Xia, Jianchuan
Abstract : Objective . Rare research of renal cell carcinoma (RCC) has been made in a comprehensive and full description based on a long period of time as yet. This study was aimed at investigating the incidence and relative survival rates (RSRs) of RCC in the past forty years and to disclose the impact of sex, race, and socioeconomic status (SES) on RCC. Methods . The data as variables, including age, gender, race, and SES, were obtained from the Surveillance, Epidemiology, and End Results (SEER) database. SES was divided into three levels: low poverty, medium poverty, and high poverty. The medium- and high-poverty groups were integrated into one group in all analyses. The RSRs were calculated using period analysis methodology. Summary statistics including incidence and RSRs were analyzed by Kaplan–Meier and Cox proportional hazards models with GraphPad Prism 8.0.1 software and Stata 12.0 software. Results . A total of 77, 513 patients diagnosed with RCC were enrolled in this study, showing an increased incidence and 10-year RSRs from 1977 to 2016 . Patients older than 60 years had the highest incidence and the lowest RSRs. This research also showed significant disparities between different groups: incidence in males, blacks, and medium-high poverty groups was higher than that in females, whites, and low poverty groups, while RSRs were lower. For sex groups, the disparity of RSRs was obvious among patients who were 30–59 years old, but not among those younger than 29 years or older than 60 years. Based on SES, the survival gaps between different SES groups were getting wider over the past forty years. Conclusion . This study showed how age, sex, race, and SES affected the incidence and RSRs of RCC, which may be beneficial for both better designed clinical trials and efficient prevention methods.